Origen and Basil of Caesarea on the Liar Paradox - DelCogliano, Mark (Augustinianum, 2011)
Both Origen and Basil of Caesarea report that some people saw Ps. 115,2 LXX - " I said in my alarm, ' Every human being is a liar ' " -- as an expression of the Liar Paradox and formulated a version of the paradox based upon it. But Ps. 115,2 is actually not susceptible to the Liar paradox, despite Origen and Basil believing it to be so. Not realizing this, both sought to undermine the possibility that Ps. 115,2 did express the Liar paradox by offering a contextual exegesis, in which they argue that the speaker of the verse, David, can be considered a god, not a human being.